SDM PERBANKAN SYARIAH DI BRUNEI DARUSSALAM - Mirza Astia Amri (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2022)
Syariah banking is a bank that operates in accordance with the principles of Islamic law. Islamic banks are not new to the banking world. We know that at the end of the 90s, many conventional banks were liquidated due to the monetary crisis, but in fact Islamic banking was able to survive and even grow. As we know, Islamic banking is also not free from obstacles in its operations and currently the biggest obstacle faced by Islamic banking is related to the quality of human resources that are inadequate and this is a challenge for Islamic banking in Brunei Darussalam. Through literature studies, this paper describes the initial conditions of Islamic banking in Brunei Darussalam, steps taken by the Sultanate of Brunei to create trained industry professionals in the Islamic finance sector by providing on the job training.